Trust in Physicians Among Rural Medicaid‐Enrolled Smokers. Issue 2 (13th August 2013) - Nelms, Emory; Wang, Ling; Pennell, Michael; Wewers, Mary Ellen; Seiber, Eric; Adolph, Michael D.; Paskett, Electra D.; Ferketich, Amy K.
Abstract Purpose Associations have been found between trusting patient‐physician relationships and use of preventive care and a greater adherence to prescribed care. The objectives of this study were to assess the level of trust rural Medicaid smokers have in their physicians and whether trust was related to patient characteristics or physician behavior. Methods This was a cross‐sectional study of smokers who were enrolled in a tobacco‐dependence treatment program. Participants were rural Medicaid‐enrolled adults, age 18 and older, who were current smokers. Participants were enrolled from 8 primary care clinics as they came in for an appointment with their physician. The Trust in Physician Scale was completed at the baseline visit. One week later, an interview was conducted with the smoker to determine whether the physician provided tobacco‐dependence treatment counseling at the visit. Mixed models were used to model the relationship between trust and participant characteristics and physician behaviors. Findings Medicaid smokers in this study exhibited a high level of trust in their health care provider, as levels were similar to those reported in the general population of patients. Trust was significantly higher among individuals with better self‐reported health. Conclusions Rural Medicaid smokers appeared to have similar levels of trust in their physician as other patients. Future research should explore the role trust plays in shaping interactions between underserved populations and physicians within the context of smoking cessation counseling.